When magic makes sense: public perceptions of modern esoteric practices in urban Indonesia - Pradipta, Andamar; Stark, Alexander (Penerbit Universiti Kebangsaan Malaysia, 2025)
Esoteric practices in Indonesia have been embodied by traditional shamanistic figures called dukuns. Dukuns who are often viewed in a negative light, perform various services such as healing, divination, or harming one’s enemy through supernatural powers. Today, as social media becomes more influential in personal branding, more esoteric practitioners try to rebrand themselves as far as possible from the dukun image, including those who perform dukun practices. Tarot reading’s rise in popularity on social media means that there is an opportunity for new esoteric practitioners to lean towards a more accessible approach to self-branding through the adoption of new-age spiritualism in their practices. This study aims to inductively explain how the general public in Indonesian urban settings shifts their perceptions toward modern esoteric practices through in-depth interviews with ten informants from the Jabodetabek (Jakarta, Bogor, Depok, Tangerang, and Bekasi) area of Indonesia. The emic perspectives of the ten informants purposively sampled from members of the public were thematically analysed through a coding process based on specific themes and subthemes. The results show that the general public has become more accepting of new-age practices such as tarot reading despite having the same negative perceptions toward traditional dukun practices. This caused the public to remain reluctant to hire the services of new-age practitioners as esotericism in Indonesia is generally still affected by the negative stigma of dukuns. Further research should be conducted not only in the context of the Indonesian culture but also in other settings or other cultures.